1991
DOI: 10.1113/jphysiol.1991.sp018664
|View full text |Cite
|
Sign up to set email alerts
|

Species‐specific transfer of plasma albumin from blood into different cerebrospinal fluid compartments in the fetal sheep.

Abstract: SUMMARY1. The blood-cerebrospinal fluid (CSF) transfer of endogenous sheep albumin and several exogenous species of albumin has been investigated in different CSF compartments of the immature fetal sheep brain, at an early stage of development (60 days gestation, term is 150 days) when the CSF concentration of total protein is high.2. There were marked differences in the steady-state CSF/plasma ratios for all species of albumin (including endogenous sheep albumin) between different CSF compartments. Ratios mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
74
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 28 publications
11
74
0
Order By: Relevance
“…Pa,,J was higher in our 60 days gestation fetuses (53+ 6 mmHg) than in the other studies. High levels of J' in 60 days gestation fetal sheep have previously been reported by Dziegielewska et al (1979Dziegielewska et al ( , 1991. The high levels in the present study may have been partly due to higherPa levels in the ewes which were all positive-pressure-ventilated (see Table 1 (Table 2).…”
Section: Discussionsupporting
confidence: 66%
“…Pa,,J was higher in our 60 days gestation fetuses (53+ 6 mmHg) than in the other studies. High levels of J' in 60 days gestation fetal sheep have previously been reported by Dziegielewska et al (1979Dziegielewska et al ( , 1991. The high levels in the present study may have been partly due to higherPa levels in the ewes which were all positive-pressure-ventilated (see Table 1 (Table 2).…”
Section: Discussionsupporting
confidence: 66%
“…On the other hand, E-CSF has a complex protein composition, and the exposure of the apical surface of neuroepithelial cells to this fluid could affect their behavior (Dziegielewska et al 1980a(Dziegielewska et al , 1980b(Dziegielewska et al , 1981(Dziegielewska et al , 1991(Dziegielewska et al , 2000Checiu et al, 1984;Gato et al, 2004). Experimental data demonstrate that the loss or modification of the composition of the E-CSF strongly decreases the neuronal cell population (Desmond and Jacobson, 1977;Desmond, 1985).…”
Section: E-csf Helps Control Cellular Behavior In Neuroepithelial Cellsmentioning
confidence: 94%
“…The absence of significant correlations (least squares) between paired CSF and plasma concentrations for endogenous rat albumin, and human and sheep albumin in 3-day-old rats (Table 2) would occur if a specific transfer mechanism for albumin (as previously suggested for the fetal sheep; Dziegielewska et al 1991) were saturated under normal conditions by high plasma albumin concentrations. The correlations between paired CSF and plasma concentrations for bovine albumin and the chemically modified albumins are consistent with the proposal that these molecules (also sucrose and inulin) are not recognized by a transport system and enter the CSF primarily by diffusion (which would be expected to be concentration dependent).…”
Section: Origin Of Csf Albuminmentioning
confidence: 99%
“…This greater permeability is thought to be due to unrestricted diffusion through large 'pores' that reduce in number rather than in diameter later in development (Dziegielewska, Evans, Malinowska, M0llgard, Reynolds, Reynolds & Saunders, 1979; Habgood, Knott & Saunders, 1992). In addition, most of the endogenous proteins in CSF in the immature brain are present in much higher concentrations than can be accounted for by diffusion (Dziegielewska, Evans, Lorscheider, Malinowska, M0llgard, Reynolds, Saunders, & Wilkinson, 1980a, Dziegielewska, Evans, Malinowska, M0llgard, Reynolds & Saunders, 1980bDziegielewska, Habgood, M0llgard, Stagaard & Saunders, 1991). Thus in fetal sheep CSF at 30 days gestation (term is 150 days) Dziegielewska (1982) and Dziegielewska et al (1980a, b) found that albumin (66 kDa), fetuin (48 kDa) and a-fetoprotein (64 kDa) which have very similar diffusion coefficients (albumin 6-1 cm2 s-' 10-1, fetuin 6-2 and a-fetoprotein 5 7), have very different natural steady-state CSF/plasma ratios (albumin 26%, fetuin 62 % and oc-fetoprotein 53°%).…”
Section: Introductionmentioning
confidence: 99%